Prognostic significance of inflammatory biomarkers in hepatocellular carcinoma following hepatic resection. Issue 4 (29th April 2019) - Itoh, S; Yugawa, K; Shimokawa, M; Yoshiya, S; Mano, Y; Takeishi, K; Toshima, T; Maehara, Y; Mori, M; Yoshizumi, T
Abstract: Background: Cancer-related inflammation has been correlated with cancer prognosis. This study evaluated inflammatory biomarkers, including neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR) and lymphocyte-to-monocyte ratio (LMR), programmed death ligand (PD-L) 1 expression, and tumour microenvironment in relation to prognosis and clinicopathological features of patients with hepatocellular carcinoma (HCC) undergoing curative hepatic resection. Methods: Patients who had liver resection for HCC in 2000–2011 were analysed. Univariable and multivariable analyses were conducted for overall (OS) and recurrence-free (RFS) survival. Immunohistochemical analyses of PD-L1, CD8 and CD68 expression were performed. HCC cell lines were evaluated for PD-L1 expression. A subgroup analysis was conducted to determine patient features, survival and the tumour microenvironment. Results were validated in a cohort of patients with HCC treated surgically in 2012–2016. Results: Some 281 patients who underwent hepatic resection for HCC were included. Multivariable analysis showed that low LMR was an independent prognostic factor of OS (hazard ratio (HR) 1·59, 95 per cent c.i. 1·00 to 2·41; P = 0·045) and RFS (HR 1·47, 1·05 to 2·04; P = 0·022) after resection. Low preoperative LMR values were correlated with higher α-fetoprotein values ( P < 0·001), larger tumour size ( P < 0·001), and high rates of poor differentiation ( P = 0·035) and liver cirrhosis ( P = 0·008). LMR was significantly lower in PD-L1-positive patients than in those with PD-L1 negativity ( P < 0·001). Results were confirmed in the validation cohort. PD-L1 expression was upregulated in HCC cell lines treated with interferon-γ and co-cultured with THP-1 monocyte cells. Conclusion: LMR is an independent predictor of survival after hepatic resection in patients with HCC. Modulation of the immune checkpoint pathway in the tumour microenvironment is associated with a low LMR. Graphical Abstract: The study shows that inflammatory biomarkers, especially the lymphocyte-to-monocyte ratio (LMR), are independent predictors of survival after hepatic resection in patients with hepatocellular carcinoma. LMR was significantly lower in programmed death ligand (PD-L) 1-positive patients than in PD-L1-negative patients. Moreover, the ratio of CD8+ to CD68+ cells was significantly lower in patients with a low LMR. Inflammatory biomarkes as prognostic factors in HCC